Depression and post-traumatic stress disorder symptoms during the COVID-19 pandemic in Italy. (20th October 2021) - Rousset, S; Camussi, E; Piccinelli, C; Senore, C; Armaroli, P; Giordano, L; Ferrante, G; Bert, F; Siliquini, R
Abstract: Introduction: Social restrictions imposed by the Italian Government during the COVID-19 emergency might have had a significant impact on mental health. The purpose of this study was to estimate the prevalence of depressive and post-traumatic stress disorder (PTDS) symptoms in a sample of Italian citizens during the first COVID-19 pandemic wave. Materials and methods: A cross-sectional survey was carried out between April and June 2020 using a snowball sampling. Depressive symptoms were explored through the Patient Heath Questionnaire-2 (PHQ-2), while the post-traumatic stress disorder (PTDS) was investigated through the SPAN (Startle, Physical arousal, Anger, Numbness) questionnaire. Poisson regression models were used to explore the association between the outcomes under study and sociodemographic/housing characteristics. Results: A total of 10.758 interviews were collected and 7.847 (73%), complete for a minimum set of indicators (age, sex, area of residence), were included in the final analysis. The majority of the respondents were females (71%). Sample mean age was 48.6 years. The prevalence of depressive symptoms was 21.2% and that of PTDS was 43.8%. Symptoms of depression and PTDS significantly diminished across age groups, in particular in people over 70 years compared with people aged 14-29 years (PR 0.65, 95% CI 0.49-0.86). A higher prevalence was found in students compared with retired people, both for depressive symptoms (PR 1.49, 95% CI: 1.05-2.10) and PTDS (PR 1.31, 95% CI: 1.02-1.69). Conclusions: Prevalence of depressive and PTDS symptoms was high, in particular among younger people and students. That could potentially lead to adverse mental health outcomes in the future, with serious public health consequences. As the pandemic emergency is not solved yet, it is necessary to implement preventive strategies in order to protect the mental well-being of particularly vulnerable subgroups in the population. Key messages: The prevalence of psychological symptoms was high in this sample during the first wave of COVID-19 pandemic. The subgroups of the population at higher risk for adverse psychological outcomes were younger people and students.